Evaluation of newton’s law learning: application of the force concept inventory: Application of the Force Concept Inventory - Hernández Suárez, Cesar Augusto; Núñez, Raúl Prada; Álvarez Macea, Fermín Rafael (Scientia et Technica, 2023)
The Force Concept Inventory is a test to determine the level of conceptual knowledge of students about mechanical physics and to evaluate the effectiveness of different teaching strategies on the conceptual component of learning. The test was applied with the purpose of knowing the level of conceptualization of the students who study the subject of Physics in a basic and medium educational institution. The results of the pre-test gave to know the students' level of conceptualization and offered information for the elaboration of workshops based on real physical situations to elaborate force diagrams. The results of the post-test allowed estimating Hake's learning gain and showed evidence about the students' conceptual evolution and information to develop future teaching activities about Newton's laws